2022
DOI: 10.3847/1538-4357/ac70c6
|View full text |Cite
|
Sign up to set email alerts
|

The Circumgalactic Medium from the CAMELS Simulations: Forecasting Constraints on Feedback Processes from Future Sunyaev–Zeldovich Observations

Abstract: It is important to understand the cycle of baryons through the circumgalactic medium (CGM) in the context of galaxy formation and evolution. In this study, we forecast constraints on the feedback processes heating the CGM with current and future Sunyaev–Zeldovich (SZ) observations. To constrain these processes, we use a suite of cosmological simulations, the Cosmology and Astrophysics with MachinE Learning Simulations (CAMELS). CAMELS varies four different feedback parameters of two previously existing hydrody… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 109 publications
1
18
0
Order By: Relevance
“…The resulting impact on the power spectrum of the cosmic matter correlation function (which is an essential measure for cosmological parameter estimation) is to increase power on scales out to which feedback can substantially redistribute the baryons. However, the SIMBA jet speed variations have the opposite effect: Increased jet speed reduces the density and pressure of the CGM [8]. Not only does every observable CGM property decrease significantly in Figure 2, but the electron density maps in Figure 1 take on a smoothed appearance.…”
Section: From Galactic Atmospheres: Perspectivesmentioning
confidence: 98%
See 2 more Smart Citations
“…The resulting impact on the power spectrum of the cosmic matter correlation function (which is an essential measure for cosmological parameter estimation) is to increase power on scales out to which feedback can substantially redistribute the baryons. However, the SIMBA jet speed variations have the opposite effect: Increased jet speed reduces the density and pressure of the CGM [8]. Not only does every observable CGM property decrease significantly in Figure 2, but the electron density maps in Figure 1 take on a smoothed appearance.…”
Section: From Galactic Atmospheres: Perspectivesmentioning
confidence: 98%
“…For example, Moser et al ( 2022) [8] found that increasing the IllustrisTNG stellar feedback input energy raised the density and pressure of the CGM as measured via the kinetic and thermal S-Z effects. Likewise, the signal of every observable CGM feature in Figure 2 increases from run 1P_3_n5 to run 1P_3_0.…”
Section: From Galactic Atmospheres: Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, several works using both data (e.g Pandey et al 2019Pandey et al , 2022Gatti et al 2022a) and simulations (e.g. Scannapieco et al 2008;Bhat-tacharya et al 2008;Moser et al 2022;Wadekar et al 2022) have shown that the tSZ signal from low-mass (group scale) halos is sensitive to feedback. Excitingly, the sensitivity of tSZ measurements is expected to increase dramatically in the near future due to high-sensitivity CMB measurements from e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Two recent works - Moser et al (2022) and Wadekar et al (2022) -have used the CAMELS simulations to explore the information content of the tSZ signal for constraining feedback. These works focus on the ability of tSZ observations to constrain the parameters of subgrid feedback models in hydrodynamical simulations.…”
Section: Introductionmentioning
confidence: 99%